Graduate Real Estate Education: Integrating the Industry - Chambers, Lisa; Holm, Jen; Worzala, Elaine (International Journal of Property Sciences (E-ISSN: 2229-8568), 2009)
In 2005, a pilot study of graduate real estate programs examined the coalescence of industry and the classroom in 14 well-recognized programs from around the world (Chambers and Worzala, 2005). This study expands the 2005 results in order to include all graduate programs listed in the tenth edition of ULI's Directory of Real Estate Development and Related Education Programs (2005) as well as graduate real estate programs certified by the Royal Institution of Chartered Surveyors (RICS)1. As in the original study, we surveyed academics within the various programs to determine how the graduate programs are enhanced by directly incorporating real estate industry professionals into the curriculum as well as how the programs provide external opportunities for graduate students to interact with business professionals. The results of this study analyse existing strategies and we hope to suggest criteria for “best practices” to apply in graduate real estate programs around the world. Strategies examined include the use of project-based courses, mentoring and shadowing programs, speaker series, internships, networking events, executive-in-residence programs, career fairs, guest lecturers, alumni associations and field trips. In addition, some questions focus on the respondents’ perceptions of the most effective strategies in foster student/industry interaction. We also queried the academics about alternative performance measurements and assessment tools that could be used in the future to rank real estate graduate educational programs.